Rebooting their systems. (Economist, 2011)
The article focuses on the U.S. computer industry companies Dell and Hewlett-Packard. The companies' efforts to adjust to the declining use of microcomputers by businesses and consumers due to the introduction of technological innovations such as tablet computers and cloud computing are discussed. The idea of "verticalization" within high technology industries, where companies produce and market hardware, computer operating systems and computer software rather than specialize, is considered.